2017
DOI: 10.1002/2017jd026676
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of optimal dispersion model source parameters using satellite detections of volcanic ash

Abstract: In this paper we demonstrate how parameters describing the geometry of the volcanic ash source for a particular volcanic ash dispersion model (Hybrid Single‐Particle Lagrangian Integrated Trajectory (HYSPLIT)) may be inferred by the use of satellite data and multiple trial simulations. The areas of space likely to be contaminated by ash are identified with the aid of various remote sensing techniques, and polygons are drawn around these areas as they would be in an operational setting. Dispersion model simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…As in the Kelut case, no retrievals were obtained by the SECO algorithm with MTSAT until at 1032 UTC on 30 May when partial retrievals were obtained. This initial eruption carried the bulk of the ash in a southeast direction relative to the summit at an altitude of about 15 km, but inverse modeling using detections of ash [ Zidikheri et al , ] suggested that ash reached as high as 20 km. A second phase of eruptions then commenced at around 1700 UTC on 30 May with both ash detection‐based inverse modeling and estimates of height based on brightness temperatures suggesting a maximum height of about 14 km.…”
Section: Some Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As in the Kelut case, no retrievals were obtained by the SECO algorithm with MTSAT until at 1032 UTC on 30 May when partial retrievals were obtained. This initial eruption carried the bulk of the ash in a southeast direction relative to the summit at an altitude of about 15 km, but inverse modeling using detections of ash [ Zidikheri et al , ] suggested that ash reached as high as 20 km. A second phase of eruptions then commenced at around 1700 UTC on 30 May with both ash detection‐based inverse modeling and estimates of height based on brightness temperatures suggesting a maximum height of about 14 km.…”
Section: Some Case Studiesmentioning
confidence: 99%
“…Manam (4.08°S, 145.04°E, 1.81 km summit elevation), located in Papua New Guinea, erupted around 0130 UTC on 31 July 2015. The growing umbrella cloud could be clearly identified soon after on Himawari‐8 satellite imagery with the bulk of the ash appearing to move toward the southwest [ Zidikheri et al , ]. SECO mass load retrievals were available soon after.…”
Section: Some Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved features of the AHI instrument, in terms of spectral, spatial and temporal resolution, should guarantee a more efficient monitoring of rapidly changing weather/environmental phenomena in comparison with imagers of the previous MTSAT series [18]. In particular, the AHI infrared bands 7 (3.74-3.96 µ m), 11 (8.44-8. Although a number of studies up to now have been performed exploiting Himawari-8 observations (e.g., [21][22][23][24]), only a few of them focused on volcanic ash (e.g., [25,26]). Some authors In this work, we investigate the ash events of 25-28 November 2017 from space by implementing the well-established RST ASH algorithm [14][15][16], which was previously tested over the Asiatic region using infrared MTSAT-1R/2 (Multi-Functional Transport Satellite-1R/2) observations [17], for the first time on Himawari-8 data.…”
Section: Datamentioning
confidence: 99%
“…The improved features of the AHI instrument, in terms of spectral, spatial and temporal resolution, should guarantee a more efficient monitoring of rapidly changing weather/environmental phenomena in comparison with imagers of the previous MTSAT series [18]. In particular, the AHI infrared bands 7 (3.74-3.96 µm), 11 (8.44-8 Although a number of studies up to now have been performed exploiting Himawari-8 observations (e.g., [21][22][23][24]), only a few of them focused on volcanic ash (e.g., [25,26]). Some authors have used, for instance, a qualitative ash RGB product designed by the JMA (Japan Meteorological Agency) [27] to discriminate ash and SO2 plumes from meteorological clouds, emphasizing the advantages of using data from Himawari-8 for monitoring those features in a timely manner [25].…”
Section: Datamentioning
confidence: 99%